2015
DOI: 10.1038/srep13749
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA NALT interaction with NOTCH1 promoted cell proliferation in pediatric T cell acute lymphoblastic leukemia

Abstract: Long non-coding RNA (lncRNA) was referred to be participating in various malignant tumors. Location based analysis of the mechanism in lncRNA and genes have been highly focused. In this study, we reported that lncRNA named NALT which was located near NOTCH1 within 100 bp away. We confirmed that up-regulation of NALT associating with NOTCH1 in human samples. Increased expression of NALT dramatically promoted cell proliferation in cell lines via CCK8 assay and EDU stain. Further xenograft tumor also indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 38 publications
(41 reference statements)
0
69
0
Order By: Relevance
“…Identification of effective disease biomarkers for prognosis is urgently required. In recent years, mounting epidemiological and molecular biological studies have demonstrated that lncRNAs dysregulation was involved in causing cancers [19,20]. By using detection analysis such as RNA sequencing and microarray, altered expression of lncRNAs has been reported in varies of malignancies, and multiple deregulated lncRNAs have been implicated in physiological and pathological processes of human cancer [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Identification of effective disease biomarkers for prognosis is urgently required. In recent years, mounting epidemiological and molecular biological studies have demonstrated that lncRNAs dysregulation was involved in causing cancers [19,20]. By using detection analysis such as RNA sequencing and microarray, altered expression of lncRNAs has been reported in varies of malignancies, and multiple deregulated lncRNAs have been implicated in physiological and pathological processes of human cancer [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs have tissue-specific expression and serve an important role in the human transcriptome by regulating normal tissue differentiation as well as cancer development (30). Notably, a number of previous studies have implicated a role of lncRNA dysregulation, of transcripts including leukemia-induced non-coding activator RNA, B-ALL-associated long RNA (BALR)-6 and -2, NOTCH1-associated lncRNA in T-ALL and CCDC26, in tumorigenicity in leukemias (31)(32)(33)(34). SNPs may significantly influence gene expression and function.…”
Section: Discussionmentioning
confidence: 99%
“…U6 snRNA was used as an internal control. The primers for detecting the expression of CYLD were 5ʹ-TCAGGCTTATGGAGCCAAGAA-3ʹand 5ʹ-ACTTCCCTTCGGTACTTTAAGGA-3ʹ.QRT-PCR was performed using an ABI Prism 7900HT instrument (Applied Biosystems) according to the directions provided with the reagents [22].…”
Section: Quantitative Real Time Polymerase Chain Reaction (Qrt-pcr)mentioning
confidence: 99%